Basic life support: experience report of a university group (Research, Society and Development, 2023)
Objective: to report the process of structuring a basic life support training group, with focus on cardiopulmonary resuscitation for laypersons. Method: this is an experience report of undergraduate nursing students and professors who participate in an extension group focused on teaching basic life support, called “Hands to Save”. The experience was presented in three stages 1) preparation of the group 2) training of the components of the group 3) performance of students and teachers in the training. Results: the training team consisted of nine members, including professors and undergraduate nursing students; the group was trained by a professional specialist in urgency and emergency accredited by the American Hearth Association; two trainings were carried out in different places, a congress in the health area and in an Army Battalion. Conclusion: The activities carried out allowed the public to recognize the care measures in case of Sudden Cardiac Death. Students were able to experience health education and develop skills and capacity to disseminate information. The Faculty and the nursing course, through the extension project, were able to disseminate knowledge and train the population, resulting in benefits for society.